Women with Gaucher Disease - Maria del Mar Meijon-Ortigueira; Isabel Solares; Cecilia Muñoz-Delgado; Sinziana Stanescu; Marta Morado; Cristina Pascual-Izquierdo; Lucía Villalon Blanco; Amaya Belanger Quintana; Covadonga Pérez Menéndez-Conde; Montserrat Morales-Conejo; Jesús Villarrubia-Espinosa (Biomedicines, 2024)
Gaucher disease is an inherited disorder in which there is a deficiency of the enzyme glucocerebrosidase, which leads to the accumulation of glucosylceramide. Although much scientific evidence is now available, there is still limited data on the impact on the different life stages of women with this disease. Among other alterations, a delay in menarche has been described, although it has not been related to fertility problems. Menorrhagia is relatively frequent, being related to the presence of thrombocytopenia, thrombocytopathies or coagulation disorders. On the other hand, pregnancy planning is an increasingly frequent concern. All patients should undergo genetic counseling, and it is important to monitor the appearance or worsening of organomegaly, bone and hematologic abnormalities to establish clinical and therapeutic recommendations. Management during the puerperium will depend on the evolution of gestation, and, during the lactation period, the potential appearance of bone complications should be assessed. An early onset of menopause, compared to the general population, has also been described, which may accelerate the development of osteopenia. Finally, although the usual screening protocols for neoplasms are currently being performed, it is recommended to watch for early signs of liver or renal neoplasms when examining the results of imaging tests performed during evaluations for this disease.